Harnessing CRISPR-Cas9 immunity for genetic engineering - Charpentier, Emmanuelle (2014)
CRISPR-Cas encodes an adaptive immune system that defends prokaryotes against infectious viruses and plasmids. Immunity is mediated by Cas nucleases, which use small RNA guides (the crRNAs) to specify a cleavage site within the genome of invading nucleic acids. In type II CRISPR-Cas systems, the DNA-cleaving activity is performed by a single enzyme Cas9 guided by an RNA duplex. Using synthetic single RNA guides, Cas9 can be reprogrammed to create specific double-stranded DNA breaks in the genomes of a variety of organisms, ranging from human cells to bacteria, and thus constitutes a powerful tool for genetic engineering. Here we describe recent advancements in our understanding of type II CRISPR-Cas immunity and how these studies led to revolutionary genome editing applications.